Improving Student Learning Outcomes by Using the Index Card Match Method in Islamic Education Subjects at SD Negeri 11 Simpang Utara - Nasir, Muhammad (MADINA : Journal of Islamic Studies, 2024)
This study aims to improve student learning outcomes in Islamic religious education learning by using the index card match method. This study is a classroom action research that uses four steps, namely planning, action, observation and reflection. The subjects of this study were elementary school students. The data for this study were obtained by test and observation techniques. Tests are used to measure learning outcomes and observations are used to analyze teacher and student learning activities. The data analysis technique used in this study is descriptive statistics by comparing the results obtained with indicators of research success. The results of the study indicate that the index card match method can improve student learning outcomes in Islamic religious education learning. This can be seen from the increase in the percentage of student learning completion in each cycle with details of the pre-cycle 44.01%, the first cycle 62.42% and in the second cycle increased to 88.16%. Thus, the use of the index card match method can be used as an alternative to improve student learning outcomes in Islamic religious education learning.